CUSTOMER LOYALTY : PT. TELKOMSEL DAN PT. XL AXIATA DI MALANG - Eric Santoso (Ma Chung Press, 2015)
This research aimed to explore the influence of relationship marketing that consists of customer service, loyalty programs, and brand community building to the customer loyalty of PT Telkomsel’s and PT. XL Axiata’s customers in Malang. This research was a quantitative study using multiple linear regression analysis. This study used a sample of 200 people (100 for Telkomsel and 100 for XL), collecting data was using the method of accidental sampling. The data was collected in several place such as Grapari Telkomsel, XL Center, and the researcher’s own house . The results of this study indicated that relationship marketing which consists of customer service, loyalty programs and brand community affect signficantly the customer loyalty. This research model which consist customer service, loyalty programs, brand community building variable are able to predict 96% of customer loyalty